PENINGKATAN KETERAMPILAN MEMBACA DAN BUDAYA LITERASI MELALUI PENERAPAN PROGRAM “PERPUSTAKAAN CERDAS” SISWA KELAS V DI SDN 2 SENDANGAGUNG TAHUN PELAJARAN 2025/2026 - Sumarianto, Febri; Putut Setiyadi, D.B.; Sriyanto, Sriyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research began with the relatively low reading skills and literacy culture of students at SDN 2 Sendangagung. Reading skills are fundamental skills, as they are the primary means for students to acquire information and knowledge. This study aims to describe the implementation and results of improving students' reading skills and literacy culture through the “Perpustakaan Cerdas” program in fifth-grade students at SDN 2 Sendangagung in the 2025/2026 Academic Year. The research model used was classroom action research with eight fifth-grade students at SDN 2 Sendangagung. The results of the study indicate that the implementation of the “Perpustakaan Cerdas” program improved reading skills and successfully fostered a culture of literacy through activities such as regular reading, the use of classroom reading corners, and discussions and reflections on reading. Based on the research results, it can be concluded that the implementation of the “Perpustakaan Cerdas” program was effective in improving the reading skills and literacy culture of fifth-grade students at SDN 2 Sendangagung in the 2025/2026 academic year. Therefore, this program can be a strategy for teaching reading skills and developing a culture of literacy in elementary schools.